2005
DOI: 10.1596/1813-9450-3588
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution Of Skilled Immigration And International Graduate Students To U.S. Innovation

Abstract: The impact of international students and skilled immigration in the United States on innovative activity is estimated using a model of idea generation. In the main specification a system of three equations is estimated, where dependent variables are total patent applications, patents awarded to U.S. universities, and patents awarded to other U.S. entities, each scaled by the domestic labor force. Results indicate that both international graduate students and skilled immigrants have a significant and positive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 56 publications
3
85
0
2
Order By: Relevance
“…We argue that this excellent performance of the Chinese with respect to other students is most likely explained by selection processes. Our findings strengthen and complement other studies that have found that migrant scientists and engineers make disproportionate contributions to U.S. innovation (Levin & Stephan 1999;Hunt 2011, Stuen, Mobarak & Maskus 2011Chellaraj, Maskus & Mattoo 2008, Gurmu, Black & Stephan 2010. The influx of talented students is an important benefit to host universities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We argue that this excellent performance of the Chinese with respect to other students is most likely explained by selection processes. Our findings strengthen and complement other studies that have found that migrant scientists and engineers make disproportionate contributions to U.S. innovation (Levin & Stephan 1999;Hunt 2011, Stuen, Mobarak & Maskus 2011Chellaraj, Maskus & Mattoo 2008, Gurmu, Black & Stephan 2010. The influx of talented students is an important benefit to host universities.…”
Section: Discussionsupporting
confidence: 89%
“…This paper contributes to the growing literature on immigration and innovation. Previous studies have typically analyzed the relationship between the innovative performance of cities (Kerr & Lincoln 2010), states (Hunt & Gauthier-Loiselle 2010), firms (Kerr & Lincoln 2010;Passerman 2011) or universities (Stuen, Mobarak & Maskus 2011;Chellaraj, Maskus & Mattoo 2008;Gurmu, Black & Stephan 2010) and the share of migrants in these entities.…”
mentioning
confidence: 99%
“…16 Immigration generally appears to raise aggregate wages and lower prices as well as stimulate investment and innovation (Peri 2010;Greenstone and Looney 2012;Hunt and Gaultier-Loiselle 2010;Chellaraj, Maskus and Mattoo 2008).…”
Section: Spillovers From the World To The United Statesmentioning
confidence: 99%
“…These trade and investment flows have become even more important with the rising share of international profits at U.S. companies, which rose from 5% in 1960s to about a quarter of all profits in 2007; there is significantly higher revenue growth potential in emerging markets than in developed markets (Aeppel 2007, Agtmael 2007, Gupta and Wang 2009. Recent studies show that international graduates and skilled immigrants make significant contributions to U.S. innovative activity in terms of total patents and patents issued to U.S. universities and other entities (Chellaraj et al 2005, Hunt and Gauthier-Loiselle 2009, Kerr and Lincoln 2010. Several other studies show that restrictive visa policies can reduce job creation and innovation opportunities in the United States (NFAP 2007(NFAP , 2008.…”
Section: Prior Literaturementioning
confidence: 99%